CTNI-30. A SNAPSHOT OF "REAL WORLD" CURRENT NEURO-ONCOLOGY PRACTICE IN TEN UK CENTRES AND RATIONALE FOR THE TESSA JOWELL BRAIN MATRIX (TJBM) PLATFORM STUDY. (12th November 2021) - Wykes, Victoria; Apps, John; Savage, Joshua; Meade, Sara; Pohl, Ute; Sawlani, Vijay; Patel, Amit; Billingham, Lucinda; Thompson, Gerard; Waldman, Adam; Ansorge, Olaf; Watts, Colin
Abstract: OVERVIEW: The TJBM Platform Study (https://www.birmingham.ac.uk/research/crctu/trials/brain-matrix ) is a programme of work aimed at improving the knowledge of, and treatment for, glioma. We present the feasibility data collected from the initial ten UK centres. METHOD: The UK TJBM centres completed a multi-disciplinary feasibility questionnaire to facilitate participation and collaboration across centres. Data were collected from hospital electronic board review records, clinic letters, operative and imaging notes, MDT or personal experience. RESULTS: Work load: Between 2016-2018 service provision redistribution reflects a trend towards higher volume centres. Overall, glioma workload within ten TJBM centres has remained stable. Imaging: All TJBM centres have good access to imaging techniques and neuroradiology expertise, including relevant 'advanced' imaging. All have RANO capability, although not widely used clinically. Neurosurgery: All centres have access to 5 ALA, perform awake craniotomy for language assessment and motor/sensory mapping are typically performed asleep, with subtle variation in techniques. Pathology: Despite molecular analysis advances, current practice is limited to the evaluation of formalin embedded tissue by traditional morphology/ immunohistochemically staining, with limited targeted testing of specific genetic changes. Clinical oncology: Oncology treatments for glioma were as per NICE guidance with some minor local variation. A relative lack of linking treatments to detailed clinical, treatment, toxicity, and quality of life data making communication of significance of findings to patients challenging. CONCLUSION: Through systematic real-world data collection the TJBM platform study will provide a detailed understanding of practice within the UK, linked to molecular tumour genotype, treatment response outcome measures, and regular quality of life assessments. This infrastructure will help establish a trial-competent network for future collaborative research. Academic and industry partners will be able to use the TJBM platform through collaboration, overseen by a strong governance framework. This will maximise the opportunities and abilities to translate advances into trials and patient benefit.